(untitled) (International Journal of Veterinary Medicine and Animal Science, 2025)
Livestock is a vital component of Bangladesh’s agricultural economy, contributing significantly to rural livelihoods and food security. Among the indigenous breeds, Red Chittagong Cattle (RCC) stand out for their adaptability, disease resistance, and dual-purpose utility in milk and meat production. Despite these advantages, RCC faces threats due to traditional management practices and limited adoption of scientific methods. This study investigates the knowledge, attitudes, and management practices of farmers rearing RCC in Anwara Upazila, Chittagong District, during January to July 2023. Data from 30 farmers, primarily male, aged 26–40, and engaged in diverse occupations, revealed a reliance on traditional management systems. Most farmers owned 6–10 RCC, provided minimal concentrate feed, and relied on naturally grown grasses for nutrition. Breeding was conducted through natural service, with an 80% conception rate and annual calving. Milk yield averaged 3.25 liters per day, demonstrating the breed’s productivity under low-input conditions. Farmers employed basic hygienic practices, with limited use of antiseptics or disinfection. Disease occurrence was minimal, with only six cases reported over six months. Vaccination was rare, limited to Foot-and-Mouth Disease (FMD). Farmers cited RCC’s resilience, low feed requirements, and adaptability as key advantages over other breeds. The findings highlight the need for targeted farmer training in modern cattle-rearing practices, improved veterinary services, and initiatives promoting RCC’s economic and genetic value. Enhancing these aspects can bolster RCC conservation and provide socio-economic benefits, contributing to sustainable rural development in Bangladesh.